Removal of Pb(II) from Aqueous Solution by Sorption on used Tea Leaves (Journal of Bangladesh Academy of Sciences, 2010)
Batch sorption study was performed using used black tea leaves (UBTL) as a low-cost adsorbent for the removal of lead (II) from aqueous solutions. Experiments were conducted as a function of contact time, initial metal ion concentration, solution pH and temperature. The sorption of Pb(II) on used tea leaves increases with increase of initial pH of solution upto a certain limit which corresponds to the pH nearly 5. The sorption isotherms follow Langmuir equation better than Freundlich equation. Again the Langmuir equation is more applicable at higher temperatures compared to those at low temperature at all pH. The monolayer sorption capacity decreases with increase in processing temperature but the overall sorbed amount increased with the increase in temperature at all pH. The positive value of estimated heat of sorption suggests the activated sorption. A probable mechanism of the sorption of Pb(II) on used tea leaves was proposed based on the surface charge of used tea leaves and the change of charge of Pb(II) with the pH of solution. DOI: 10.3329/jbas.v33i2.4100 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 2, 167-178, 2009